Management of Retrosternal Goiter without Sternotomy: A Case Report - Tandililing, Sherly; Sipayung, Edwin Z. (Medical Scope Journal, 2025)
Abstract: Retrosternal goiter (RG) is a thyroid enlargement that extends into the chest, often causing compression of nearby structures such as trachea and esophagus. Thyroidectomy for RG is a complex procedure, with the choice of surgical approach depending on the goiter’s size and position. A cervical approach is typically preferred, though sternotomy may be required in some cases. We reported a 57-year-old female presented with a 20-year history of a progressively enlarging neck lump, which extended from the right to the left side, neck vein enlargement, and radiating pain. Laboratory tests were within normal limit. Pathology biopsy revealed a follicular thyroid nodule with a Bethesda II classification and imaging revealed a multinodular goiter causing compression of the trachea. This case was classified as type A with a pyramidal shape, apex pointing downward, type I with location in the anterior mediastinum, and Grade I with location above the aortic arch (at the level of T4); so, sternotomy was not required, considering the potential complications associated with sternotomy. The patient was then diagnosed with toxic retrosternal goiter in the euthyroid phase and underwent a total thyroidectomy without sternotomy. Postoperative care included fluids, antibiotics, H2 blocker, and analgesics. The patient showed good recovery, with no complications or symptoms of thyrotoxicosis at the two-week follow-up. In conclusion, in this case surgical intervention is focused on releasing decompression, and a total thyroidectomy was performed without sternotomy. An important technique that can be shared is to remove surgically the superior pole first, releasing it from Berry’s ligament on one of the lobes and should always free the tissue as close to the goiter tissue as possible to avoid damage to the surrounding structures. The successful outcomes in studies emphasize that with careful assessment, retrosternal goiter can be safely treated with minimal complications. Keywords: retrosternal goiter; non-sternotomy procedure